Relationship between corn harvest index and phosphorus efficiencies through trail (Research, Society and Development, 2021)
The productivity of different crops, including corn, is influenced by the ability of plants to absorb and use nutrients. The objective was to verify, through trail analysis, the direct and indirect relationships between the harvest index and the efficiency of phosphorus use in corn. The study variables were: corn harvest index (HI), phosphorus harvest index (FO), compartmentalized use efficiency on the leaf (CF), compartmentalized use efficiency on the stem (CC), compartmentalized use efficiency on the straw (CP), efficiency of use compartmentalized in the grain (CG), efficiency of use integrated in the leaf (IF), efficiency of use integrated in the stem (IC), efficiency of use integrated in the straw (IP). Through Pierson's correlation, we observed a high and positive correlation between CP and IP, CF and IF and IC and FO. There was a strong and negative correlation between: IC and IP, IC and CP and FO and CG. O It was concluded that the variables that obtained the greatest direct and positive effects on the corn harvest index were: harvest index for phosphorus and efficiency of compartmentalized use in the grain. Direct and negative effects on the corn harvest index were: efficiency of compartmentalized use in the straw and efficiency of compartmentalized use in the leaf. Indirectly, the trail analysis showed that efficiency of compartmentalized use in the grain and efficiency of integral use in the leaf are strongly positively correlated, and in the opposite direction, efficiency of compartmentalized use in the grain and harvest index for phosphorus are negatively correlated.